Assessing the factors of green computing adoption among manufacturing employees: an analysis of the electrical and electronic sector - Aziati, H. Nor; Ping, Chai Sui; Ahmad, Md Fauzi; Abdullah, Nor Hazana; Ismail, Siti Nor Ziah (American Scientific Publishers, 2018)
Recent trends and heavy uses of IT products and electronic gadgets have led to a proliferation of green computing studies because these wastes are not biodegradable. A significant amount of previous studies has been performed on green computing at the organizational level with most studies tend to focus on developed countries. The present study examined numerically the most influential factor towards the employees’ intention to adopt green computing and measure the intention level of employees in green computing adoption. The current study explored five adoption factors with five hypotheses have been established. These hypotheses were theorized from Theory of Planned Behaviour with emphasis on environmental concern. Previous studies from Malaysia context have primarily concentrated on green computing in education sector compared to manufacturing sector. Hence the study was conducted at electrical and electronic industries located at southern Malaysia. Questionnaires were purposely distributed to 250 respondents, however only 110 responses were valid that yielded response rate of 56%. Respondents are among the employees in IT and administration department that equipped with ICT application. The finding verifies the most influential factor affecting green computing adoption is environmental concern with 43.8%. All factors were proved to have positive correlation to the green computing intention. This correlation is related to the high intention level of employees in practicing green computing due to headquarters initiatives and the conditions set by the importing countries. Social norms have less impact towards behavioral intention to practice green computing that manifested by the low correlation percentage. The current study contributes to our knowledge on the green computing intention among manufacturing employees in Malaysia besides the implications of the results and future research directions. This study will help the policy makers in promoting environmental awareness among users of computing devices.